Radiation of plane sound waves by a rigid circular cylindrical pipe with a partial internal impedance loading - Demir, A; Büyükaksoy, A (S Hirzel Verlag, 2003)
Radiation of sound waves from a rigid circular cylindrical pipe with a partial internal impedance loading is investigated rigorously by a modified version of the Wiener-Hopf technique. The solution involves a set of infinitely many expansion coefficients satisfying an infinite system of linear algebraic equations. The numerical solution of this system is obtained for different parameters of the problem such as the pipe radius, internal surface impedance and their effects on the diffraction phenomenon are shown graphically.